Hubungan Tingkat Pengetahuan Lansia dengan Kejadian Reumatik di Panti Tresna Werda Minaula Kendari Tahun 2016 - Herianto, Herianto (Jurnal Gizi Ilmiah, 2016)
Clean and Healthy Lifestyle Behavior (PHBS) is a health behavior that in Indonesia in 2014 the incidence of rheumatic disease reached two million with the ratio of female patients three times that of men suffering from rheumatic disease. Rheumatism is a disorder in the form of stiffness, swelling, pain and redness in the joints and surrounding tissues, rheumatic symptoms are usually symmetrical, which attacks the same joints on both sides of the body. The problem in this study is that there is a relationship between the level of knowledge and the incidence of rheumatism in the elderly at Tresna Werda orphanage. Minaula kendari in 2016. The review of the theory is to discuss the relationship between the level of knowledge and the incidence of rheumatism in the elderly. This research was conducted on April 28 to May 09 2016, with analytical descriptive method using a cross sectional study approach. The study population was all patients with rheumatism. The sample consisted of 38 people. The independent variable in this study is knowledge (knowing, understanding, application), while the dependent variable is the incidence of rheumatism. This study uses the chi square test. The results showed that there was a relationship between Tofu and the incidence of rheumatism at the Tresna Werda Minaula Kendari social institution, because the p value (0.14) was smaller than 0.05. Most of them know about the incidence of rheumatism is still not enough or enough, amounting to 32 people (84.2%). There is a relationship between understanding and the incidence of rheumatism at the Tresna Werda Minaula Kendari Social Institution, because the P value (0.03) is smaller than 0.05. Most of them know enough about the incidence of rheumatism, amounting to 32 people (84.2%). There is a relationship between the application and the incidence of rheumatism at the Tresna Werda Minaula Kendari social institution, because the P value (0.14) is smaller than 0.05. Most of them know enough about the incidence of rheumatism, amounting to 32 people (84.2%). Suggestions are expected to be the basis for providing preventive measures against rheumatic diseases